1-Phenyl-2-trifluoromethyl-4-quinolone - Hossaini Sadr, Moayad (International Union of Crystallography, 2007)
In the title molecule, C(16)H(10)F(3)NO, the N-bound phenyl ring is oriented nearly orthogonal to the quinolinyl ring in order to avoid steric clashes with the trifluoromethyl substituent [dihedral angle 89.7 (1)°].